Multimodal neuroimaging transcends time in thrombolysis for pediatric stroke - Tai, Waimei Amy; Sanossian, Nerses; Partikian, Arthur; Mogensen, Monique; Jones, Jesse; Liebeskind, David S. (Journal of Pediatric Neuroradiology, 2012)
Pediatric stroke is particularly challenging because of its variable presentation and relative rarity. Diagnosis of pediatric stroke is often delayed while other diagnoses are considered, unfortunately leading to a loss of therapeutic opportunity. Recent research advances in adult stroke such as multimodal imaging and a clinical trial showing benefits in extending the therapeutic window for thrombolytics are likely to have important implications in pediatric stroke. We describe the case of a 13-year-old boy presenting with acute stroke where multimodal magnetic resonance imaging with perfusion and permeability images allowed safe treatment with thrombolysis outside the standard treatment time window.
Keywords: Multimodal MRI; thrombolysis; stroke; children